Measuring general sense of agency: a Japanese adaptation and validation of the sense of agency scale (J-SoAS) - Xu, Wenzhen; Legaspi, Roberto; Ishikawa, Yuichi; Washida, Yuichi (Frontiers in Psychology, 2024)
The Sense of Agency (SoA) refers to the individual's perception of control over actions and their subsequent impact on the external environment. SoA encompasses multiple dimensions, such as implicit/local and explicit/general, which can be quantitatively assessed through cognitive tasks and psychometric questionnaires, respectively. The explicit and general aspect of SoA is commonly evaluated using the Sense of Agency Scale (SoAS), introduced by Tapal et al. ( 2017). This study's objective is to adapt and validate a Japanese version of the Tapal-SoAS. To achieve this, we distributed an online survey in three stages, gathering data from 8,237 Japanese participants aged between their 20s and 60s. Our analysis confirmed the bifactorial structure identified in the original study: the Sense of Positive Agency (SoPA) and the Sense of Negative Agency (SoNA). Metrics pertaining to test-retest reliability, internal consistency, and construct validity reached satisfactory thresholds. Furthermore, the two-factor models demonstrated suitable fit across various age cohorts. The Japanese version of the SoAS (J-SoAS) shows potential for cross-cultural comparisons of explicit and general SoA, particularly between Western and Eastern populations, and among distinct age groups, including young adults and the elderly.